2001
DOI: 10.1007/s004660000222
|View full text |Cite
|
Sign up to set email alerts
|

3-D Modeling of nanoindentation experiment on a coating-substrate system

Abstract: The validity of indentation tests for the characterization of the mechanical properties of coatings relies greatly on the indentation depth. Deep indentation concludes to unreliable results due to the substrate effect on the measured properties. At shallow depths the size effect can also be an important error factor. The purpose of the present study is the determination of the critical ratio of coating thickness to indentation depth, up to which the substrate properties have a negligible effect on the force ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…The decrement of PDMS surface modulus could be easily attributed to substrate effect, as discussed in a previous work involving a hard thin film on a soft substrate. 60,61 The variations of these mechanical properties as a function of depth indicated that the thickness of the cross-linked layer was less than 100 nm, as shown in Figure 10; and we need to establish another method for measure the cross-linking depth.…”
Section: Mechanical Properties and Thickness Of Cross-mentioning
confidence: 99%
“…The decrement of PDMS surface modulus could be easily attributed to substrate effect, as discussed in a previous work involving a hard thin film on a soft substrate. 60,61 The variations of these mechanical properties as a function of depth indicated that the thickness of the cross-linked layer was less than 100 nm, as shown in Figure 10; and we need to establish another method for measure the cross-linking depth.…”
Section: Mechanical Properties and Thickness Of Cross-mentioning
confidence: 99%
“…1a). This method allows us to calculate deformation and stress fields (stress concentrations) [29][30][31] including plastic deformation of substrates which is impossible by applying only extended Hertz theory for coating-substrate systems [32,33]. In our models the mesh was densified close to the contact zone to the indenter, where significant stress concentration was expected (Fig.…”
Section: Simulationmentioning
confidence: 99%
“…a soft coating on a hard substrate system. Vlachos et al (2001) also considered a hard film on a soft substrate material system that was assumed as elastic perfectly plastic, but they used 3D FE models.…”
Section: Introductionmentioning
confidence: 99%